In Utero and Early Life Exposure to the Great Chinese Famine and Risk of Rheumatoid Arthritis in Adulthood. Issue 4 (7th March 2021) - VanEvery, Hannah; Yang, Wen‐hao; Olsen, Nancy; Zhang, Xinyuan; Shu, Rong; Lu, Bing; Wu, Shouling; Cui, Liufu; Gao, Xiang
Abstract : Objective: To investigate whether early life exposure to the Great Chinese Famine of 1959−1961 is associated with the risk of RA development in adulthood. Methods: This study included 101, 510 participants who were enrolled in the Kailuan Study in 2006. RA cases were confirmed by medical record review. Logistic regression was used to calculate the odds ratio (OR) and 95% confidence interval (95% CI) for RA according to famine exposure status (exposed in utero or between ages 0 and 3 years, between ages 3 and 6 years, or at age 6 years or older), in comparison to participants born after 1961 who were not exposed to famine. Results: During 12 years of follow‐up (2006−2018), we identified 187 RA cases. Individuals exposed to famine in utero or between ages 0 and 3 years had a higher prevalence of RA relative to other groups (0.2−0.35% versus 0.08−0.20%). After adjustment for potential confounders, the OR for RA was 2.95 (95% CI 1.55−5.59) for individuals exposed in utero, 4.53 (95% CI 2.72−7.54) for those exposed between ages 0 and 3 years, 2.55 (95% CI 1.43−4.57) for those exposed between ages 3 and 6 years, and 2.72 (95% CI 1.70−4.36) for those exposed at age 6 years or older versus individuals born after 1961. Similar associations with the risk of RA were observed for men and women when subjects were stratified by sex ( P for interaction = 0.89). Conclusion: Individuals exposed to famine in utero or in early childhood (between ages 0 and 3 years) were more likely to develop RA in adulthood, highlighting the importance of early life as a vulnerable developmental period.